Comparison of marginal adaptation, internal fitness and microleakage of Zolid, Zirconia and Empress 2 all-ceramic crown materials (An in vitro study) (Mustansiria Dental Journal, 2018)
The purposes of this in vitro study were to compare the marginal adaptation,internal fitness and the microleakage of three CAD-CAM all ceramic crownsmaterials: Zolid, Zircon, and Empress 2. This study also evaluated the correlation ofmicroleakage of these ceramic crowns materials to the marginal fitness.Forty-five maxillary first premolar teeth were prepared with 2-mm occlusalreduction and 1-mm all around shoulder finish line, teeth were randomly divided intothree main groups according to the type of ceramic material that was used (n=15).Group 1: received a CAD-CAM Ceramill Zolid® unilayered transparent zircon Group2: received a CAD-CAM Ceramill ZI units (Zirconium oxide) Group 3: received aCAD-CAM Ceramill wax units that would subsequently invested and heat pressed tofabricate a hot-press ceramic crowns.The results showed statistical significant difference in marginal fitness, internalfitness and microleakage between Zolid group and other groups (P>0.0001). Therewas highly significant correlation of the marginal and internal fitness, whilst there wasno significant correlation marginal fitness and microleakage.,